PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DENGAN FERMENTASI KOTORAN PADAT DAN URIN SAPI YANG DIPERKAYA PUPUK TSP - Fitri sari dewi; Armaini Armaini; Islan Islan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of the research is to find out the best dose against the growth of seedlings of cacao. This research was carried out experimentally using a Complete Randomized Design (CRD) with 5 treatments and 4 replication, so that there were obtained 20 units experimental each unit countain 2 plant. The treatmentsof fermented manure dosage with TSP fertilizer enriched are: 0 ml/plant,250 ml/plant, 500 ml/plant,750 ml/plant, and 1000 ml/plant. Data obtained from research results are analyzed statistically and further test Duncan's New Multiple Range Test (DNMRT) level of 5%. The observed parameters werecrop, height increase the number of leaves, stem diameter, dry weight and root shoots ratio. The results showed that giving doses of 750 ml/plant gives influenced the growth of seedlings of cocoa and cocoa seedling growth can increase seen in high value added plant parameters, number of leaves, stem diameter, and dry weight of cocoa seedlings.The application of the fermentation of solid dung and urine TSP fertilizer enriched cow can increase the growth of seedlings of cocoa looks at the crop height increase, number of leaves, stem diameter, and dry weight of cocoa seedlings. fermentation of solid dung and urine enriched cow manure is best at doses of TSP dosing 750 ml/plant. the dose is 1000 ml/plant, no longer affected the growth of the seedlings.Keyword : The growth of, cacao seedlings, fermentation, solid dung and cow urine, TSP fertilizer